Superfícies mínimas : primeira e segunda variação da área - Almeida, Sebastião Carneiro de (1975)
With these notes we intend to study the First and Second Formulas of the Variation in a Riemannian manifold as well as to give a concrete application to the case of a surface of the R to the cube. The problem of determining whether a certain surface with a given boundary has the smallest possible area is treated. The work consists of four chapters. The first chapter is a basic exposition of varieties immersed in a Riemannian variety. The concepts and results of Riemannieana Geometry that would be used later were sufficiently treated here. Chapters II and III are demonstrations of the First and Second Formulas of Variation. Chapter IV is an application of these formulas